Penerapan Program Literasi Dasar Di Sekolah Dasar 138 Dan 193 Negeri Pekanbaru - Fitri Nabila; Anggi Rozma Yusmita; Aisyah Aulia Fajhriany; Febrina Dafit (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2023)
The purpose of this observation activity is to see the development and application of basic literacy in elementary schools. In compiling this article, a pedescriptive type of research was carried out using a qualitative approach, to obtain an overview of the implementation of basic literacy in elementary schools. Based on the results of interviews conducted by group 6 with school principals, teachers and students at SDN 138 and SDN 190 Pekanbaru, regarding how the implementation of basic literacy is implemented in elementary schools and how programs are implemented to improve basic literacy in two schools, namely Public Elementary School 138 and Public Elementary School 193 Pekanbaru, found similarities and differences in the implementation of basic literacy in these two schools. As for the explanation of the stages of the school literacy movement, the first is the habituation stage. At this stage it can be done by getting used to reading for approximately 15 minutes before learning. To support this activity, of course, schools are expected to be able to provide books other than textbooks and other reading materials so that students are interested in reading. Second, is the development stage, which is the next stage after reading habits begin to form, the development of students' literacy skills can be carried out through various literacy activities.